PREPARATION OF THIN-FILM TRITIUM SOURCES FOR DETERMINATION OF THE NEUTRINO MASS - Holmes, P; Jelley, N; Williams, S; Alizadeh, R (1988)
Very thin tritium sources have been prepared, using the Langmuir-Blodgett technique of multilayer deposition, for the determination of the neutrino mass. The method of manufacture of these tritium sources is described.